2012
DOI: 10.1016/j.jmii.2011.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Astrovirus gastroenteritis in hospitalized children of less than 5 years of age in Taiwan, 2009

Abstract: Astrovirus accounted for 1.6% of infections in children under 5 years hospitalized with acute gastroenteritis in Taiwan. Compared with those caused by rotavirus, the incidence of gastroenteritis in hospitalized children caused by astrovirus was low and the disease severity was mild.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Although the majority of the Classic HAstV cases were observed in autumn 2011, HAstV‐1 was the only one of the three genotypes detected that was also observed in 2012, and considering 2011, was also detected in summer. The high prevalence of HAstV‐1 observed in this study, is in agreement with others studies showing that this genotype is the most prevalent in the Latin American region and worldwide …”
Section: Discussionsupporting
confidence: 93%
“…Although the majority of the Classic HAstV cases were observed in autumn 2011, HAstV‐1 was the only one of the three genotypes detected that was also observed in 2012, and considering 2011, was also detected in summer. The high prevalence of HAstV‐1 observed in this study, is in agreement with others studies showing that this genotype is the most prevalent in the Latin American region and worldwide …”
Section: Discussionsupporting
confidence: 93%
“…The peak of rotavirus infections occurred in March–May and November–January months which was similar with the findings of other studies [Nguyen et al, ; Lou et al, ; Ouyang et al, ; Sai et al, ]. However, different seasonal patterns have been observed in other three viral pathogens, the studies showed that the peak incidence of AstV was in summer months from April to June in Taiwan [Tseng et al, ], a higher frequency of HuCV infection from July to September in Ningxia, China [Zhan et al, ], and AdV infection cases peaked in July in Tianjin, China [Ouyang et al, ]. The study also showed that the peak of AstV, AdV, and HuCV infections appeared earlier than that of rotavirus infections.…”
Section: Discussionsupporting
confidence: 87%
“…It implies that traditional measures used to improve hygiene and sanitation may not prevent the enteric viral infection significantly. To explore the effective prevention and control strategies of viral agents‐induced diarrhea, the pathogens’ epidemiology of viral infections has been examined in some studies based on hospitalization and outpatients’ surveillance [Duan et al, ; Lou et al, ; Ouyang et al, ; Tseng et al, ; Chen et al, ; Lu et al, ; Yu et al, ; Zhang et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Novel HAstVs are part of the neurovirulent astroviruses, which also include animal astroviruses (30). Other unexpected clinical manifestations recently associated with human and animal astroviruses include respiratory tract infections (31)(32)(33)(34)(35)(36)(37), fever of unknown etiology (38,39), hepatitis (40,41), and severe gout in geese (42). Altogether, these findings suggest that there are probably other still unrecognized divergent astroviruses with clinical implications beyond gastroenteritis in humans and animals.…”
mentioning
confidence: 95%